Effects of manipulating volume and intensity training in masters swimmers - Pugliese, L.; Porcelli, S.; Bonato, M.; Pavei, G.; La Torre, A.; Maggioni, M. A.; Bellistri, G.; Marzorati, M. (International Journal of Sports Physiology and Performance, 2015)
Purpose: Recently, some studies have suggested that overall training intensity may be more important than training volume for improving swimming performance. However, those studies focused on very young subjects, and/or the difference between high-volume and high-intensity training was blurred. The aim of this study was to investigate in masters swimmers the effects of manipulation of training volume and intensity on performance and physiological variables. Methods: A group of 10 male masters swimmers (age 32.3 ± 5.1 y) performed 2 different 6-wk training periods followed by 1 wk of tapering. The first period was characterized by high training volume performed at low intensity (HvLi), whereas the second period was characterized by low training volume performed at high intensity (LvHi). Peak oxygen consumption (VO2peak) during incremental arm exercise, individual anaerobic threshold (IAT), and 100-m, 400-m, and 2000-m-freestyle time were evaluated before and at the end of both training periods. Results: HvLi training significant increased VO2peak (11.9% ± 4.9% [mean change ± 90%CL], P = .002) and performance in the 400-m (-2.8% ± 1.8%, P = .002) and 2000-m (-3.4% ± 2.9%, P = .025), with a likely change in IAT (4.9% ± 4.7%, P > .05). After LvHi training, speed at IAT (12.4% ± 5.3%, P = .004) and 100-m performance (-1.2% ± 0.8%, P = .001) also improved, without any significant changes in VO2peak, 2000-m, and 400-m. Conclusions: These findings indicate that in masters swimmers an increase of training volume may lead to an improvement of VO2peak and middle- to long-distance performance. However, a subsequent period of LvHi training maintains previous adjustments and positively affects anaerobic threshold and short-distance performance.